2013
DOI: 10.1183/09031936.00133012
|View full text |Cite
|
Sign up to set email alerts
|

Target lobe volume reduction and COPD outcome measures after endobronchial valve therapy

Abstract: Endobronchial valve (EBV) therapy may be associated with improvements in chronic obstructive pulmonary disease-related outcomes and may therefore be linked to improvements in the body mass index, airflow obstruction, dyspnoea, exercise capacity (BODE) index.Data from 416 patients with advanced emphysema and hyperinflation across Europe and USA, who were randomised to EBV (n5284) or conservative therapy (n5132) were analysed. Quantitative image analysis was used to compare the volume of the targeted lobe at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 35 publications
3
64
0
1
Order By: Relevance
“…10 Endobronchial treatments are still in investigational phases; preliminary results are varied and may suff er from the lack of a precise imaging biomarker. Recently, it has been shown that quantitative CT scan target volume 11 and regional perfusion 12 analysis may help to identify lobar exclusion and to select the most responsive patients to endobronchial valve treatment. Measurements of changes in specifi c gas volume (SVg) via CT scan may not only be an excellent biomarker but may also provide specific regional information that can aid in surgical planning and evaluation posttreatment.…”
mentioning
confidence: 99%
“…10 Endobronchial treatments are still in investigational phases; preliminary results are varied and may suff er from the lack of a precise imaging biomarker. Recently, it has been shown that quantitative CT scan target volume 11 and regional perfusion 12 analysis may help to identify lobar exclusion and to select the most responsive patients to endobronchial valve treatment. Measurements of changes in specifi c gas volume (SVg) via CT scan may not only be an excellent biomarker but may also provide specific regional information that can aid in surgical planning and evaluation posttreatment.…”
mentioning
confidence: 99%
“…Therefore, real volume reduction seems to be also an important point for a better outcome. Complication rates such as COPD exacerbations were the same in all groups [18].…”
Section: Zephir Valvementioning
confidence: 67%
“…A retrospective study of the VENT results indicated that there was a significant correlation between TLVR and the success of EBV implantation (20). Improvements in the BODE index (more than 1 point) were observed in 67% of patients with a TLVR > 50%, 37% of patients with a TLVR of 20-50%, and 41% of patients with a TLVR < 20% (p = 0.011 for intergroup differences).…”
Section: Tlvrmentioning
confidence: 97%